Five Crossroads on the Way to Basic Income: An Italian Tour - Ugo Colombino (Institute for the Study of Labor (IZA), 2014)
The current Italian income support policies are defective with respect to both efficiency and equity. A more effective design must face five crucial choices: universal vs. categorical policies; transfers vs. subsidies; unconditional vs. means-tested policies; coverage; flat vs. progressive tax rules. Using a microeconometric model and a social welfare methodology, we simulate the effects of 30 versions of three basic types: guaranteed minimum income, unconditional basic income and wage. The simulation preserves fiscal neutrality and adopts a methodology that allows for market equilibrium and ensures a consistent comparative statics interpretation of the results. The social welfare optimal policy is an unconditional transfer coupled with a wage subsidy, with a total benefit amounting to about 70% of the poverty level, or – depending on the social welfare criterion – a pure unconditional transfer amounting to 100% of the poverty level.
Keywords: H31; H21; C25; 330; income support mechanisms; basic income; guaranteed minimum income; wage subsidies; tax reform simulation